Corrosion protection of iron by polypyrrole coatings electrosynthesised from a surfactant solution - Lehr, Ivana Leticia (2007)
This work is a study of the electropolymerisation of pyrrole onto iron electrodes in the presence of sodium bis(2-ethylhexyl) sulfosuccinate in a wide pH interval. The characterisation of the films was done using electrochemical techniques, SEM/EDX and IR spectroscopy. We show that it is possible to synthesise homogeneous, adherent and very compact films in the pH range between 7 and 12 under potentiodynamic, galvanostatic and potentiostatic conditions without substrate dissolution. The effects of various parameters on electrodeposition were investigated. The new procedure for the electrochemical synthesis of polypyrrole results in improved anticorrosion properties. The inhibition is proposed to be due to the sum of a repulsion of chloride ions because AOT remains entrapped in the polymer matrix and the presence of the iron oxide. Advantages of the use of surfactants in the electropolymerisation solution are discussed.